ACCURACY OF COMPUTERISED TOMOGRAPHY IN DIAGNOSIS OF BRAIN TUMOURS IN CHILDREN - Khan, Khalid; Qureshi, Ahmed Nadeem; Bibi, Phool; Jehanzeb, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: CT scan has replaced most of the invasive techniques in diagnosis of brain tumours because it can accurately demonstrate, localize and characterize the brain tumours. The objective of this study was to observe the accuracy of CT scan in the diagnosis of brain tumours in children by comparing it with histopathology. This descriptive case series was conducted at Department of Radiology, Ayub Teaching Hospital Abbottabad from 10th March 2005 to 9th March 2007. Methods: Both pre and post contrast CT scan was carried out on 120 patients referred to Radiology Department for CT scan suspected of having brain tumours. Data of CT findings/diagnosis of patients having brain tumours were collected on a proforma. Histopathology of specimen from operation or biopsy was carried out and compared with the CT scan diagnosis. Results: Glial tumours comprised the largest category 68 (56.67%). Medulloblastoma was 23 (19.16%) Craniopharyngioma 8 (6.63%) and Ependymoma were 6 (5.0%) each. Hemangioblastoma 2 (1.67%), Choroid plexus one (0.83%) adenoma and pineal tumours were 9 (3.33%) each. As regards comparison between CT and histopathology, an agreement between the two was found in 104 (86.67%) cases whereas in 16 (13.33%) of the cases, the histopathology reports were different. In case of Astrocytomas 63 (92.64%) were confirmed on histopathology and 5 (7.36%) was reported differently. In Medulloblastomas 19 (82.60%) were accurately diagnosed on CT scan. Sensitivity of CT scan in diagnosis of brain tumours in children was 93.33%. Conclusion: CT Scan is more accurate predictor of brain tumour yet it is not always 100% accurate. Keywords: CT scan, Histopathology, Paediatric tumours, Astrocytomas, Medulloblastoma